Royal College of General Practitioners Research and Surveillance Centre (RCGP RSC) sentinel network: a cohort profile. Issue 4 (20th April 2016) - Correa, Ana; Hinton, William; McGovern, Andrew; van Vlymen, Jeremy; Yonova, Ivelina; Jones, Simon; de Lusignan, Simon
Abstract : Purpose: The Royal College of General Practitioners Research and Surveillance Centre (RCGP RSC) is one of the longest established primary care sentinel networks. In 2015, it established a new data and analysis hub at the University of Surrey. This paper evaluates the representativeness of the RCGP RSC network against the English population. Participants and method: The cohort includes 1 042 063 patients registered in 107 participating general practitioner (GP) practices. We compared the RCGP RSC data with English national data in the following areas: demographics; geographical distribution; chronic disease prevalence, management and completeness of data recording; and prescribing and vaccine uptake. We also assessed practices within the network participating in a national swabbing programme. Findings to date: We found a small over-representation of people in the 25–44 age band, under-representation of white ethnicity, and of less deprived people. Geographical focus is in London, with less practices in the southwest and east of England. We found differences in the prevalence of diabetes (national: 6.4%, RCPG RSC: 5.8%), learning disabilities (national: 0.44%, RCPG RSC: 0.40%), obesity (national: 9.2%, RCPG RSC: 8.0%), pulmonary disease (national: 1.8%, RCPG RSC: 1.6%), and cardiovascular diseases (national: 1.1%, RCPG RSC: 1.2%). Data completeness in risk factors for diabetic population is high (77–99%). We found differences in prescribing rates and costs for infections (national: 5.58%, RCPG RSC: 7.12%), and for nutrition and blood conditions (national: 6.26%, RCPG RSC: 4.50%). Differences in vaccine uptake were seen in patients aged 2 years (national: 38.5%, RCPG RSC: 32.8%). Owing to large numbers, most differences were significant (p<0.00015). Future plans: The RCGP RSC is a representative network, having only small differences with the national population, which have now been quantified and can be assessed for clinical relevance for specific studies. This network is a rich source for research into routine practice.